Kinetics of competing exchange of oxygen and water at the surface of functional oxides. Issue 4 (20th January 2021) - Thoréton, Vincent; Niania, Mathew; Kilner, John
Abstract : Kinetics of concomitant exchange reactions of oxygen from molecular oxygen and from water are determined from IEDP SIMS experiments. Abstract : The presence of water vapour in the input gas stream influences the performance of air electrodes of solid oxide cells. In this work, the oxygen transport kinetics were determined by isotopic exchange depth profiling at 350 °C on polycrystalline La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ samples in humidified oxygen, comparing the differences in tracer diffusion profile using either 18 O2 or H2 18 O as the labelling medium. The apparent surface exchange coefficients of oxygen were determined in each case and used together to estimate the oxygen surface exchange coefficients of molecular oxygen and water. It was found that, in humid conditions, the surface exchange coefficient of molecular oxygen is significantly decreased in comparison to a reference in dry conditions. In addition, the surface exchange coefficient of water is higher than that for molecular oxygen. This is in good agreement with the hypothesis that, water monopolises the active exchange sites at the material surface and thus oxygen from water exchanges faster than the one of molecular oxygen.